Drosophila integrin adhesion complexes are essential for hemocyte migration in vivo - Moreira, Carolina G A (2017)
We thank Angela Dias for the technical help and the Jacinto group members for insightful discussions. The work was supported by a fellowship (SFRH/BD/62345/2009) to C.G.A.M. and a grant (PTDC/SAU-OBD/101259/2008) from Fundacao para a Ciencia e Tecnologia, and a European Research Council Starting Grant (2007-StG-208631).